Are Military Regimes Really Belligerent?. (July 2018) - Kim, Nam Kyu
Does military rule make a state more belligerent internationally? Several studies have recently established that military autocracies are more likely than civilian autocracies to deploy and use military force in pursuit of foreign policy objectives. I argue that military regimes are more likely to resort to military force because they are located in more hostile security environments, and not because they are inherently aggressive. First, I show that rule by military institution is more likely to emerge and exist in states facing external territorial threats. Second, by examining the relationship between military autocracies and conflict initiation, I find that once I control for states' territorial threats, the statistical association between military regimes and conflict initiation disappears. Additionally, more evidence suggests that civilian dictatorships are more conflict-prone than their military counterparts when I account for unobserved dyad heterogeneity. The results are consistent across different measures of international conflict and authoritarian regimes.